A Career That Soars Without Sacrifices Life Harmony: A New Paradigm Through Gps (Goal, Path, Self) and Energy Management - Helen Sabrina Efendi (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
The old paradigm that career success requires significant sacrifices to one’s personal life has long dominated professional culture. However, recent empirical research suggests that this perspective is not only flawed but also counterproductive. This article explores how professionals can achieve career success while maintaining life balance through an innovative approach called self-operating system enhancement, which incorporates a GPS (Goal, Path, Self) framework and an emphasis on energy management. By synthesizing cutting-edge research literature from across disciplines, we identify that work–life balance is not merely an important moderating variable but rather an accelerator of long-term career success. Research shows that effective energy management is more significant than traditional time management in creating sustained productivity. By integrating three key pillars—meaningful goal setting, measurable strategy selection, and self-awareness development—professionals can navigate their careers and personal lives simultaneously and harmoniously. This framework is supported by findings from a systematic literature review of more than 100 peer-reviewed articles. Research shows that consistent boundary-setting, structured wellness routines, and mature self-awareness are key to achieving sustained success without sacrificing mental and physical well-being.